The heparin-binding domain of VEGF165 directly binds to integrin αvβ3 and VEGFR2/KDR D1: a potential mechanism of negative regulation of VEGF165 signaling by αvβ3 - Takada, Yoko K.; Yu, Jessica; Ye, Xiaojin; Wu, Chun-Yi; Felding, Brunie H.; Fujita, Masaaki; Takada, Yoshikazu (Frontiers in Cell and Developmental Biology, 2024)
VEGF-A is a key cytokine in tumor angiogenesis and a major therapeutic target for cancer. VEGF165 is the predominant isoform of VEGF-A and it is the most potent angiogenesis stimulant. VEGFR2/KDR domains 2 and 3 (D2D3) bind to the N-terminal domain (NTD, residues 1-110) of VEGF165. Since removal of the heparin-binding domain (HBD, residues 111-165) markedly reduced the mitogenic activity of the growth factor, it has been proposed that the HBD plays a critical role in the mitogenicity of VEGF165. Here we report that αvβ3 specifically bound to the isolated VEGF165 HBD, but not to the VEGF165 NTD. Based on docking simulation and mutagenesis, we identified several critical amino acid residues within the VEGF165 HBD required for αvβ3 binding, i.e. Arg123, Arg124, Lys125, Lys140, Arg145, and Arg149, by docking simulation and mutagenesis. We discovered that the VEGF165 HBD binds to the KDR domain 1 (D1) and identified that Arg123 and Arg124 are critical for KDR D1 binding by mutagenesis, indicating that the KDR D1-binding and αvβ3-binding sites overlap in the HBD. Full-length VEGF165 mutant (R123A/R124A/K125A/K140A/R145A/R149A) defective in αvβ3 and KDR D1 binding failed to induce ERK1/2 phosphorylation, integrin β3 phosphorylation, KDR phosphorylation and did not support proliferation of endothelial cells, although the mutation did not affect KDR D2D3 interaction with VEGF165. Since β3 knockout mice are known to show enhanced VEGF165 signaling, we propose that the binding of KDR D1 to the VEGF165 HBD, and KDR D2D3 binding to the VEGF165 NTD are critically involved in the potent mitogenicity of VEGF165. We propose that binding competition between KDR and αvβ3 to the VEGF165 HBD, endow integrin αvβ3 with regulatory properties to act as a negative regulator of VEGF165 signaling.